TENSILE STRENGTH AND VIOLENT CONNECTION LAS STEEL ST 40 WITH EMPLOYING VARIATIONS ELECTROTECHNICS AND VARIATIONS OF CURRENT - Masri Bin Ardin (Universitas Sultan Ageng Tirtayasa, 2018)
Shield Metal arc welding (SMAW) is one of ways which are usually used for welding steel low carbon. The quality of the welding connection can be grouped by using pull testing, and Vickers method. This study aims to know the strength of pulling and hardness welding connection with the variation of electrodes and current. This study used carbon steel ST 40 with an electrode which is used E 6010 and E 7016 with the current variations 80 ampere, 90 ampere and 100 ampere. The result produced the result to the power of certainly drag out from a current of 80 a use electrodes 6010 was recorded at 34,92 kg / mm2. Of tensile strength with a current of 90 a shall be 37.43 kg / mm2 and tensile strength the use of a 100 a shall be 40,63. The force of attraction to the electrode 7016 is promoting the creation of ampere 80 is 33,11 kg / mm2, ampere 90 of tensile strength him it is the same 35,57 kg / mm2 while using ampere 100 of tensile strength that is produced is 37,76 kg / mm2. The difference between the value of the force of attraction for a current is 80 a 1,81 kg / mm2. A current of 90 a 1,86 kg / mm2 and with a current of 100 a 2,87 kg / mm2 for the material structure image on the fault of drag monitoring shows the material is ductile because the fault looks low and high.